Exposure to IQOS ads and reduced exposure claims, and association with perceived risk from COVID-19 on IQOS purchase and use intentions: results from a web-based survey - Sharma, Akshika; Fix, Brian; Hyland, Andrew; Bansal-Travers, Maansi; Quisenberry, Amanda; O’Connor, Richard (Frontiers in Public Health, 2024)
Introduction- IQOS was authorized to be marketed as a reduced exposure product by FDA in October 2020 during the global COVID-19 pandemic. Those who smoke may be more sensitive to reduced exposure marketing claims and may have an increased inclination towards IQOS use. We evaluated the likelihood of trying and purchasing IQOS as a function of exposure to ad, product appeal, and COVID-19 risk perceptions using the original IQOS ads with reduced exposure marketing. Method- An online cross-sectional survey recruited 604 U.S. adults (18-45 years), both who smoke and do not smoke. Participants saw one of the six randomly assigned IQOS ads with or without reduced exposure claims and answered questions about product appeal and likelihood to try and purchase IQOS. Generalized linear models were used to examine associations. Results- A per unit increase in product appeal was associated with a greater likelihood of purchasing (B=0.17, 95% CI: 0.15-0.18) and trying IQOS (B=0.16, 95% CI= 0.14-0.18). Current smokers and former e-cigarette users reported greater intentions to try IQOS compared to never smokers and never e-cigarette users respectively. Likelihood to purchase IQOS was associated with greater confidence in not contracting COVID-19 (B=0.11, 95% CI: 0.01-0.21). No significant differences were observed between different ad conditions. Current (B= -0.34, 95% CI=-0.50-(-0.19)) and former (B= -0.92, 95% CI=-0.15-(-0.68)) cigarette smokers who were someday e-cigarette users reported less intentions to purchase IQOS compared to never e-cigarette users. Whereas never smokers who were someday (B=0.58, 95% CI= 0.27-0.89; B=0.68, 95% CI= 0.39-0.98) and former e-cigarette (B=0.38, 95% CI= 0.15-0.61) users reported greater intentions to purchase and try IQOS respectively. Discussion - IQOS may have a higher product appeal especially for those who currently smoke and those who have lower risk perceptions from COVID-19. Among never smokers, those who currently use or have used e-cigarettes in past may be more receptive to IQOS marketing. The data is informative for potential trends in use of IQOS in future and may have implications for marketing regulations of HTPs.